2013
DOI: 10.1161/strokeaha.113.001125
|View full text |Cite|
|
Sign up to set email alerts
|

Early Prediction of Delayed Cerebral Ischemia After Subarachnoid Hemorrhage

Abstract: All patients were derived from the prospectively collected cohort of SAH patients admitted to our hospital. The development cohort originated from a previously described study population of patients admitted between January 1999 and June 2007.9 Three-hundred seventy-one patients met the following inclusion criteria (1) SAH confirmed by computed tomography (CT) or lumbar puncture; (2) aneurysm proven by means of CT/MR-or catheter angiography; (3) admitted within 3 days after onset; (4) at least 1 follow-up scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 26 publications
5
86
2
Order By: Relevance
“…24 The VASOGRADE derived from the studies published by de Rooij et al 15 and Crobeddu et al, 16 who developed risk charts to predict who would or would not develop DCI, respectively, combining the WFNS 9 and the modified Fisher scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 The VASOGRADE derived from the studies published by de Rooij et al 15 and Crobeddu et al, 16 who developed risk charts to predict who would or would not develop DCI, respectively, combining the WFNS 9 and the modified Fisher scales.…”
Section: Discussionmentioning
confidence: 99%
“…The main idea was to create an ease-to-remember, ease-to-use, and practical grading system that would allow clinicians to tailor monitoring strategies and treatment aggressiveness according to the different grades. The VASOGRADE derived from previously published studies by de Rooij et al 15 and Crobeddu et al, 16 which showed clinical condition on admission and the amount of blood on CT (associated with age), as the major risk factors for DCI and DCI-related cerebral infarction. This analysis represents, therefore, the external validation of de Rooij et al, 15 in a large and diverse sample of SAH patients.…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…16 We and others have observed relationships between Fisher grade, HH score, and increasing age with acute and/or long-term outcomes. 17,18 Our multivariate analysis showed that 20-HETE CSF levels/trajectory groups remained strongly associated with acute and long-term outcomes and mortality after controlling for Fisher grade and HH score, respectively. These studies suggest that 20-HETE may serve as a potential biomarker of acute and long-term outcomes and mortality in patients with aSAH.…”
Section: Discussionmentioning
confidence: 80%
“…Early brain injury (EBI), which occurs in the acute phase, and delayed cerebral ischemia (DCI) may be primarily involved in such sequelae related to subarachnoid hemorrhage. [3][4][5][6] As the simplest parameter that represents the grade of EBI, the World Federation of Neurological Surgeons (WFNS) grade has been used. A study reported that the outcome was poorer in highergrade patients.…”
Section: Introductionmentioning
confidence: 99%